Bahan Ajar Keterampilan Menulis Berbasis Higher Order Thinking Skills (HOTS) di PBA IAIN Madura - Maisaroh, Siti; Amin, Moh. Badruddin; Fajriyah, Khomisatul (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This research addresses the following issues: (1) Writing skills teaching materials provided by lecturers are theoretical rather than practical. (2) The second writing skill, emphasized in reading classes, focuses on reading Arabic texts without vowels, pronunciation, letter articulation, and translation, without advancing students’ higher-level reading skills. The study aims to: (1) develop writing skill materials based on Higher-Order Thinking Skills (HOTS), (2) assess their validity, and (3) measure their effectiveness. This research follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), using observation, interviews, documentation, questionnaires, and tests for data collection. Findings indicate: (1) Writing materials were developed in textbook form, integrating HOTS principles, student needs, and real-world topics to enhance inferential analysis, evaluation, and creation. (2) Expert validation showed high feasibility: 94.62% for teaching materials, 87.25% for reading skills, 85% for learning technology, and 92% for language, classifying them as